Pretargeted PET Imaging of trans-Cyclooctene-Modified Porous Silicon Nanoparticles - Keinanen O; Makila EM; Lindgren R; Virtanen H; Liljenback H; Oikonen V; Sarparanta M; Molthoff C; Windhorst AD; Roivainen A; Salonen JJ; Airaksinen AJ (AMER CHEMICAL SOC, 2022)
Pretargeted positron emission tomography (PET) imaging based on bioorthogonal chemical reactions has proven its potential in immunoimaging. It may also have great potential in nanotheranostic applications. Here, we report the first successful pretargeted PET imaging of trans-cyclooctene-modified mesoporous silicon nanoparticles, using F-18-labeled tetrazine as a tracer. The inverse electron-demand Diels-Alder cycloaddition (IEDDA) reaction was fast, resulting in high radioactivity accumulation in the expected organs within 10 min after the administration of the tracer. The highest target-to-background ratio was achieved 120 min after the tracer injection. A clear correlation between the efficiency of the in vivo IEDDA labeling reaction and the injected amount of the tracer was observed. The radioactivity accumulation decreased with the increased amount of the co-injected carrier, indicating saturation in the reaction sites. This finding was supported by the in vitro results. Our study suggests that pretargeted imaging has excellent potential in nanotheranostic PET imaging when using high-specific-activity tracers.